IoT-Galvanized pandemic special E-Toilet for generation of sanitized environment. (19th May 2022) - Gupta, Amit Kumar; Gothwal, Pushpa; Goyal, Dinesh; Travieso-Gonzalez, Carlos M.
Abstract: The entire world is enmeshing the pandemic COVID-19, which affected the public health and it is spread all over the world. Every country's authority is making more and more efforts towards maintaining the public health as well as mental health and are developing the vaccination to control the COVID-19. As COVID-19 is an infected disease for which a sanitized environment must be chosen at top most priority to prevent infection. Most of the countries are facing the problem of incrementing the infection rate of COVID due to griminess problems. Most healthcare industries are also working to create a sanitized environment with incorporation of the Internet of Things (IoT) which is resulting in the smart health care appliances for generating the sanitized environment. In this paper the researchers have developed an IoT- Galvanized Pandemic Special E-Toilet for generation of sanitized environment which resolves the issues of griminess problem. The proposed architecture has been comprising with three levels of working methodology as Occupancy Check, Auto Flush and Auto control of Appliances using Mobile Application. It is implemented using a raspberry pi board, Arduino Uno as a core unit of the system with interfacing the peripherals: IR sensor, Ultrasonic sensor and HC05 Bluetooth module, servo motor, Relay module, CFL lamp and LED. The proposed architecture has been simulated individually using single piece of sensor, then later assembled all the peripheral together and simulated. The proposed architecture can be used in field of education, industries, corporate offices, multiplexes, hospitals etc.